2008
DOI: 10.1038/nm1738
|View full text |Cite
|
Sign up to set email alerts
|

Neurotensin increases mortality and mast cells reduce neurotensin levels in a mouse model of sepsis

Abstract: Sepsis is a complex, incompletely understood and often fatal disorder, typically accompanied by hypotension, that is considered to represent a dysregulated host response to infection. Neurotensin (NT) is a 13-amino-acid peptide that, among its multiple effects, induces hypotension. We find that intraperitoneal and plasma concentrations of NT are increased in mice after severe cecal ligation and puncture (CLP), a model of sepsis, and that mice treated with a pharmacological antagonist of NT, or NT-deficient mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
100
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 120 publications
(112 citation statements)
references
References 45 publications
3
100
0
7
Order By: Relevance
“…[1][2][3][4][5][7][8][9][10][11]13 We therefore decided to examine the role of mast cells and mast cell-derived TNF in another model of severe bacterial infection. S. typhimurium is a Gram-negative intracellular pathogen that causes a deadly systemic infection in mice that resembles typhoid fever in humans.…”
Section: Mast Cell-derived Tnf Can Contribute To Bacterial Proliferatmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][7][8][9][10][11]13 We therefore decided to examine the role of mast cells and mast cell-derived TNF in another model of severe bacterial infection. S. typhimurium is a Gram-negative intracellular pathogen that causes a deadly systemic infection in mice that resembles typhoid fever in humans.…”
Section: Mast Cell-derived Tnf Can Contribute To Bacterial Proliferatmentioning
confidence: 99%
“…Studies conducted using genetically mast cell-deficient (WB/ReJ ϫ C57BL/6)F 1 [1][2][3][4][5][6][7][8][9][10][11][12][13] defined herein as infections that result in relatively low mortality in normal mice. Although mast cells can contribute to host defense against bacteria by multiple direct and indirect mechanisms, [1][2][3][4][5][7][8][9][10][11][12][13] several groups have focused on the potential role of mast cell-derived tumor necrosis factor (TNF) in such settings. [1][2][3][4][5]7 Results obtained in work using TNFdeficient mice 4 or mice in which the actions of TNF are blocked by neutralizing antibodies 1,2 have clearly demonstrated that TNF can have protective functions during some bacterial infections, and that such TNF-dependent effects may include the enhancement of neutrophil recruitment and/or function and the promotion of bacterial clearance.…”
mentioning
confidence: 99%
“…To examine the potential role of NT in fat deposition and obesity, we initially compared NT-deficient mice 10,11 to wild type littermates fed a standard diet (18% kcal from fat) for 6 months. Average body length, small bowel weight and length, villus height and crypt number did not differ between genotypes (Extended Data Fig.…”
mentioning
confidence: 99%
“…This alternative approach is particularly interesting for studying the role of a protein whose deficiency induces embryonic lethality in mice, and therefore for which BMCMCs deficient for this protein cannot be generated. Both BMCMCs and ESCMCs can also be transduced in vitro with lentiviruses encoding genes of interest or shRNA to silence genes of interest, before engraftment of these cells into MC-deficient mice 31,33 .…”
Section: Discussionmentioning
confidence: 99%